Level of mercury and copper in groundwater at Pulau Burung sanitary landfill - Azlinda, Abdul Ghani; Suffian, Mohd Yusoff, Dr.; Naimah, Ibrahim; Ragunathan, Santiagoo; Saiful Azhar, Saad; Salwa, Mohd Zaini Makhtar (Malaysian Institute of Chemistry, 2008)
Organized by Malaysian Institute of Chemistry, 23rd - 25th August 2007 at Putra World Trade Centre, Kuala Lumpur.